Appendix | Attracting Highly Skilled Migrants to Guangzhou, China: A Policy Commentary - Wei Li; Ling Ma; Yining Tan; Meixin Liu (Revue Internationale de Politique de Développement)
Appendix to the chapter Wei Li, Ling Ma, Yining Tan and Meixin Liu (2022) Attracting Highly Skilled Migrants to Guangzhou, China: A Policy Commentary, International Development Policy | Revue internationale de politique de développement 14 | 2022, URL: http://journals.openedition.org/poldev/4825